P3.117 Intravaginal Practices and HIV Acquisition Among Women at High Risk For Infection in Tanzania and Uganda. (13th July 2013) - Francis, S C; Ao, T T; Watson-Jones, D; Baisley, K; Wijgert, J van de; Vandepitte, J; Bukenya, J; Grosskurth, H; Hayes, R J
Abstract : Background: Intravaginal practises (IVP) are highly prevalent in sub-Saharan Africa and may facilitate HIV transmission. In two microbicide feasibility cohorts in North-West Tanzania and Kampala, Uganda, we describe baseline prevalence of IVP and investigate associations between IVP and HIV acquisition prospectively. Methods: We enrolled HIV-negative women who worked in bars, guesthouses and similar facilities in Tanzania and sex workers and bar workers in Uganda, and followed them quarterly for 12 and 18 months, respectively. At each visit, participants were tested for HIV and interviewed about IVP in the past 3 months. We assessed the association between IVP at each follow-up visit and HIV acquisition using Poisson regression in a combined analysis of both cohorts, controlling for potential confounders. Results: 1611 participants were enrolled (966 Tanzanians; 645 Ugandans). At enrolment, 92% of Tanzanians and 93% of Ugandans reported ever cleansing inside the vagina (Table 1); the majority who cleansed used soap/soapy water at least once (75% of Tanzanians and 58% of Ugandans). Nearly half (49%) of Ugandans, but only 13% of Tanzanians, reported ever inserting a substance inside the vagina. The most common substances inserted were herbs, petroleum-based jelly, detergents, aerated drinks, honey, and salt. 1472 participants contributed 71 seroconversions/1, 780 pyrs. HIV incidence was 3.99/100 pyrs. Incidence was lower among women who reported cleansing in the past 3 months (aRR:0.44, 95% CI: 0.21–0.93). HIV incidence was similar in women cleansing with soap and those not cleansing/cleansing with water only. Inserting detergent (aRR:3.05, 95% CI: 1.30–7.18) or petroleum-based jelly (aRR:2.52, 95% CI: 1.08–5.89) were associated with HIV incidence. Conclusions: Intravaginal cleansing was highly prevalent in both cohorts; however, insertion was more common among Ugandans. Cleansing was not a predictor of HIV in this study, and may be protective; however, some substances used for insertion may be harmful. These rarer and more harmful types of IVP warrant further investigation.